2021
DOI: 10.3389/fimmu.2021.696803
|View full text |Cite
|
Sign up to set email alerts
|

Oral Administration of Lactococcus lactis Producing Interferon Type II, Enhances the Immune Response Against Bacterial Pathogens in Rainbow Trout

Abstract: Lactic acid bacteria are a powerful vehicle for releasing of cytokines and immunostimulant peptides at the gastrointestinal level after oral administration. However, its therapeutic application against pathogens that affect rainbow trout and Atlantic salmon has been little explored. Type II interferon in Atlantic salmon activates the antiviral response, protecting against viral infection, but its role against bacterial infection has not been tested in vivo. In this work, through the design of a recombinant lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 72 publications
0
9
0
Order By: Relevance
“…Few studies have also documented the capacity of lactic acid bacterial members to protect cultured fish from bacterial pathogens. Santibañez et al (2021), for instance, reported that Lactococcus lactis protected Rainbow trout ( Oncorhynchus mykiss ) from Lactocossis . Similarly, Fečkaninová et al (2019) reported that lactic acid bacterial consortia ( Lactobacillus plantarum , Lactobacillus fermentum and Lactobacillus brevis ) had antagonistic activity towards salmonid pathogens including Aeromonas salmonicida subsp.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have also documented the capacity of lactic acid bacterial members to protect cultured fish from bacterial pathogens. Santibañez et al (2021), for instance, reported that Lactococcus lactis protected Rainbow trout ( Oncorhynchus mykiss ) from Lactocossis . Similarly, Fečkaninová et al (2019) reported that lactic acid bacterial consortia ( Lactobacillus plantarum , Lactobacillus fermentum and Lactobacillus brevis ) had antagonistic activity towards salmonid pathogens including Aeromonas salmonicida subsp.…”
Section: Introductionmentioning
confidence: 99%
“…Recombinant probiotics have also been used to express proteins that stimulate the immune response in fish, such as cytokines [ 145 , 146 ] and chemokines [ 147 ], the intestinal barrier [ 148 ], or enzymes that disrupt chemical communication in pathogens [ 149 ]. In the case of the cytokines, L. lactis has been used to deliver Interferon I and II, conferring protection against IPNV and F. psychrophilum , respectively [ 145 , 146 ].…”
Section: Recombinant Probiotics In Aquaculturementioning
confidence: 99%
“…The mechanisms underlying post-viral bacterial infections are based on multifactorial processes mediated by interactions between viruses, bacteria, and the host immune system [85][86][87], and may be summarized as the disruption of commensal microbiota homeostasis [88]. Since the effects of probiotics inoculation have never been sufficiently reported, its stimulatory impact on cytokine release should be mentioned at this point [89] (Scheme 2). Dysbiosis in the respiratory and gastrointestinal tract, which in turn may alter subsequent immune function against secondary bacterial and fungal infection, were focused on the beneficial changes in the microbial compositions in this review [84,[90][91][92].…”
Section: Microbiota Influence Rt and Clinical Datamentioning
confidence: 99%
“…Other current clinical trials explored the effectiveness of Lactobacillus plantarum and L. coryniformis as dietary supplements, or Lactococcus lactis via nasal irrigation in the context of COVID-19 [92]. Besides the release of IFN-α [93], IFN-γ, IL-2, and IL-12 from lactic acid bacteria (LAB) [89,90], TNF-α upregulation through a wide range of Lactobacilli [92], reduced viral entry through Bacillus subtilis [94], the production of defensins due to Lactobacillus casei [92] and the inhibition of chemokine responses related to Bifidobacterium animalis were described [95]. Enhancing the proliferation of potentially pathogenic bacterial species was limited.…”
Section: Microbiota Influence Rt and Clinical Datamentioning
confidence: 99%
See 1 more Smart Citation